Developing the Ideal Teacher in the Digital Era to Improve the Quality of Education According to Rusdi Ahmad Tha'imah - Abd Halim; Ach Muhlis (Penerbit Presisi Pustaka, 2026)
This article explores Rusdi Ahmad Tha’imah’s concept of the ideal teacher in the era of digitalization and its relevance to improving the quality of Islamic education. Tha’imah emphasizes al-jaudah al-syāmilah, a holistic approach to educational quality encompassing personal integrity, scientific competence, and professional performance. Amid the rapid transformations brought by digital technology—such as technological demands, ethical challenges, and shifting learning interactions—teachers are expected to integrate spirituality, professionalism, and digital adaptability. This study employs a descriptive-analytical approach by examining Tha’imah’s educational thought and linking it to 21st-century teacher competencies. The findings indicate that Tha’imah’s ideas remain highly relevant in shaping the model of an ideal teacher today: a murabbi who combines digital literacy, pedagogical excellence, moral values, and a culture of quality leadership. Through this integration, Islamic education can sustain innovative, humanistic, and value-based learning processes despite the dynamic nature of digital environments.